SOCIO-PHILOSOPHICAL ANALYSIS OF SOCIETY'S MODERNIZATION (Scientific journal of the Fergana State University, 2023)
In this article, we aimed to study the essence of the concept of modernization, the approaches formed to it. In it, the important features of the process of modernization of the political, economic, social, and cultural spheres of society were scientifically based, and the specific aspects of the reforms carried out in the way of establishing a free civil society in our country were analyzed.Methods such as systematic analysis, comparison, generalization, and deduction were used to study the nature and forms of modernization.The analysis of literature on the topic showed that modernization is a comprehensive process that represents the establishment of new, modern, advanced social and economic relations, characterized by the emergence of paradigmatic changes in science.Modernization means not only westernization, the transition from traditional to modernity, but also the achievement of social, political, legal, and economic development while preserving the important aspects of national identity, the transition to a society with full provision of people's welfare and human rights and freedoms.